Stoichiometry and localization of the stator subunits E and G in Thermus thermophilus H+-ATPase/synthase. - Esteban, O; Bernal, R; Donohoe, M; Videler, H; Sharon, M; Robinson, C; Stock, D (2008)
Proton-translocating ATPases are central to biological energy conversion. Although eukaryotes contain specialized F-ATPases for ATP synthesis and V-ATPases for proton pumping, eubacteria and archaea typically contain only one enzyme for both tasks. Although many eubacteria contain ATPases of the F-type, some eubacteria and all known archaea contain ATPases of the A-type. A-ATPases are closely related to V-ATPases but simpler in design. Although the nucleotide-binding and transmembrane rotor subunits share sequence homology between A-, V-, and F-ATPases, the peripheral stalk is strikingly different in sequence, composition, and stoichiometry. We have analyzed the peripheral stalk of Thermus thermophilus A-ATPase by using phage display-derived single-domain antibody fragments in combination with electron microscopy and tandem mass spectrometry. Our data provide the first direct evidence for the existence of two peripheral stalks in the A-ATPase, each one composed of heterodimers of subunits E and G arranged symmetrically around the soluble A(1) domain. To our knowledge, this is the first description of phage display-derived antibody selection against a multi-subunit membrane protein used for purification and single particle analysis by electron microscopy. It is also the first instance of the derivation of subunit stoichiometry by tandem mass spectrometry to an intact membrane protein complex. Both approaches could be applicable to the structural analysis of other membrane protein complexes.